An Analysis of Parents' Reports on Educational Services for Their Children with Albinism. (November 2018) - Corn, Anne L.; Lusk, Kelly E.
Introduction: The purpose of this study was to gain information from parents in the United States about their children with albinism. The first article (in this issue) focused on the data from this study that addressed medical and low vision care. This article focuses on information and services related to the education of children with albinism. Methods: An online questionnaire was used to collect data for this study from parents of children with albinism. Representing 223 children with albinism from 40 states in the U.S., 192 parents completed surveys and had opportunities to submit additional information. Results: A snapshot of the data indicates that, as a whole, parents perceive their children to do well academically, but they experience social and emotional challenges; 98 children were receiving direct instruction from a teacher of students with visual impairments and 84 were receiving consultation services. Although parents were generally satisfied with their level of involvement in the development of their children's education plans, many could not provide key information about the assessments their children had received, their children's reading rates, or the services with which their children were being provided. Discussion: These data illuminate the fact that, despite the premise of the Individuals with Disabilities Education Act (IDEA, 2004) that parents be equal partners in the education of their children with special needs, these parents of children with albinism were not as informed about the assessments and services that their children were receiving as might be expected. Findings also suggest the possibility that students with albinism may not be receiving appropriate educational services to address the limitations imposed by their low vision. In particular, it appears that these students, most of whom will be non-drivers, are not receiving orientation and mobility services. In addition, there was evidence that over half of these children may not be receiving instruction in the use of low vision devices. Implications for practitioners: The data gathered in this study provide directions for educators who work with children who have albinism and their families, as well as for those who design and administer services for children with visual impairments. Based on these reports from parents, it appears that children with albinism are not being assessed in the areas key to understanding their functioning and, although as a group they are doing well academically, other needs related to the Expanded Core Curriculum (ECC) are not being addressed as frequently. Teachers of students with visual impairments may want to be more explicit when describing to parents the assessments on which their educational recommendations are being made. Further research is needed to determine if children with low vision are being provided with educational services based on educational assessments and needs or if other administrative factors are driving these services.